Evaluasi Pengelolaan Aset TI dengan IT Service Management pada PT PLN (Persero) UP3 Palembang - Innatsa Saffa Tarisha; Mulyati Mulyati (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
This research was conducted to evaluate IT asset management using the IT Service Management approach at PT PLN (Persero) UP3 Palembang. This research focuses on the ITIL V3 framework with the service operation domain which includes service desk management, incident management, RACI, IT assets and networks. The results of this research show that although IT asset management is already at a fairly good maturity level with a maturity value at level 3 "defined", there are several areas that require improvement, such as service response speed, more structured incident management, and documentation of the IT asset life cycle. Maturity level evaluation and gap analysis show that there is a gap between current conditions and the expectations set, which requires improvement in various areas. This research provides recommendations regarding improvements to service desk procedures, incident management, IT asset management, and network maintenance, to improve operational efficiency and service quality. By implementing appropriate recommendations, PT PLN (Persero) UP3 Palembang is expected to be able to more optimally support operations and improve the quality of service to customers.